Bulk regional viral injection in neonatal mice enables structural and functional interrogation of defined neuronal populations throughout targeted brain areas - Cheetham, Claire E. J.; Grier, Bryce D.; Belluscio, Leonardo (Frontiers in Neural Circuits, 2015)
The ability to label and manipulate specific cell types is central to understanding the structure and function of neuronal circuits. Here, we have developed a simple, affordable strategy for labeling of genetically-defined populations of neurons throughout a targeted brain region: Bulk Regional Viral Injection (BReVI). Our strategy involves a large volume adeno-associated virus (AAV) injection in the targeted brain region of neonatal Cre driver mice. Using the mouse olfactory bulb (OB) as a model system, we tested the ability of BReVI to broadly and selectively label tufted cells, one of the two principal neuron populations of the OB, in CCK-IRES-Cre mice. BReVI resulted in labeling of neurons throughout the injected OB, with no spatial bias towards the injection site and no evidence of damage. The specificity of BReVI labeling was strikingly similar to that seen previously using immunohistochemical staining for cholecystokinin (CCK), an established tufted cell marker. Hence, the CCK-IRES-Cre line in combination with BReVI can provide an important tool for targeting and manipulation of OB tufted cells. We also found robust Cre-dependent reporter expression within three days of BReVI, which enabled us to assess developmental changes in the number and laminar distribution of OB tufted cells during the first three postnatal weeks. Furthermore, we demonstrate that BReVI permits structural and functional imaging in vivo, and can be combined with transgenic strategies to facilitate multi-color labeling of neuronal circuit components. BReVI is broadly applicable to different Cre driver lines and can be used to regionally manipulate genetically-defined populations of neurons in any accessible brain region.